2014
DOI: 10.1002/jcph.428
|View full text |Cite
|
Sign up to set email alerts
|

Safety considerations of mammalian target of rapamycin inhibitors in tuberous sclerosis complex and renal transplantation

Abstract: Rapamycin-related mTOR inhibitors (rapalogs) possess immunosuppressive and antiproliferative properties. Their mechanism of action makes them attractive therapies for several disease states but also potentiates adverse effects associated with these drugs. The oral mTOR inhibitor everolimus was recently approved for the treatment of tuberous sclerosis complex (TSC)-associated renal angiomyolipoma. As clinical use of rapalogs for the treatment of TSC increases, nephrologists and urologists who treat both childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 47 publications
1
9
0
1
Order By: Relevance
“…[20] Menstrual irregularities are reported in about a third of postmenarchal women treated with mTOR inhibitors but no longterm data are yet available with regard to a possible effect on fertility. [23] In this study, all six patients demonstrated SEGA tumor shrinkage of greater than 50% when treated with an mTOR inhibitor at therapeutic doses (4-5 mg/m 2 ), which is consistent with the existing evidence. However, the results demonstrate that sub-therapeutic doses of sirolimus (<2.5 mg/m 2 ) are not sufficient to maintain SEGA response on MRI.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…[20] Menstrual irregularities are reported in about a third of postmenarchal women treated with mTOR inhibitors but no longterm data are yet available with regard to a possible effect on fertility. [23] In this study, all six patients demonstrated SEGA tumor shrinkage of greater than 50% when treated with an mTOR inhibitor at therapeutic doses (4-5 mg/m 2 ), which is consistent with the existing evidence. However, the results demonstrate that sub-therapeutic doses of sirolimus (<2.5 mg/m 2 ) are not sufficient to maintain SEGA response on MRI.…”
Section: Discussionsupporting
confidence: 91%
“…In patients who have had transplants, sirolimus has been used in combination with other immunosuppressants since 1996 . Long‐term use of mTOR inhibitors in these patients is generally associated with toxicities that are more minor and easier to treat compared to other immunosuppressants . mTOR inhibitors have been introduced in the treatment of patients with TSC as early as 2004 and may be used for several indications in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It remains unclear whether the perioperative use of TORKinibs would be well tolerated and safe. More detailed elaboration on the safety considerations of mTOR inhibitors can be found in a recent review .…”
Section: Molecular Biology Of Mtorcsmentioning
confidence: 99%